P99 A case of unsuspected pulmonary emboli in child with lymphoma. (6th June 2017) - Pacilio, A; Gorgoglione, S; Petraccaro, A; Manca, E; Pianella, V Verrotti Di; Maggio, A; Spirito, A; Miglionico, L; Santis, R De; Ciliberti, A; Maruzzi, M; Ladogana, S; et al.
Abstract : Background: Pulmonary embolism (PE) is a potentially lethal condition. Although it's usually manifested with severe symptoms causing right ventricular dysfunction or haemodynamic instability, in case of partial arterial obstruction it can be asymptomatic. Cancer patients are at high risk of thromboembolic complications. The use of contrast-enhanced computerised tomography for cancer staging has documented a high incidence of asymptomatic PE. Case presentation: We present a case of unsuspected PE in paediatric oncology patient. A 10-year-old boy presented with cervical and axillary lymph node swellings. No response to antibiotic therapy. Infectivological tests (mononucleosis, tuberculosis, toxoplasmosis…) were negative. Staging imaging revealed a positron emission tomography/computed tomography (PET-CT) avid anterior mediastinal lymph node. There weren't liver, spleen and lung injury. Excisional biopsy of the lymph node was consistent with an anaplastic large cell lymphoma ALK+, t(2;5). After positioning of central venous catheter (CVC), the patient began treatment with chemotherapy with reduction of the lymphadenopathy. Subsequently, repositioning of CVC due to malfunction and displacement. After three months, he performed restaging; CT showed bilateral thromboembolism of the pulmonary arteries with partial obstruction. Echocardiogram showed a blood pressure's increase in pulmonary artery (PAP 38 mmHg) but the child didn't present respiratory and cardiac symptoms. Echo-color-doppler didn't report venous thrombosis of the legs. Laboratory tests showed high platelet count. d-dimer levels and activated partial thromboplastin time value were increased. Inflammatory markers (C-reactive protein, erythrocyte sedimentation rate) were normal. The patient discontinued chemotherapy and started standard anticoagulant treatment. Two weeks later, CT and ultrasound controls displayed substantial reduction of the obstruction of the pulmonary arteries and decrease of PAP. Conclusions: Thromboembolic complications are frequent in children with lymphoma. Often, routine thoracic MDCT examinations of paediatric oncology patients reveal cases of unsuspected PE. It is necessary to identify children at an increased risk for the development of PE to define an appropriate management. However, recent studies have showed that the lack of diagnosis and treatment do not have a negative influence on patient outcome.